An error analysis on Turkish EFL learners' writing tasks - Berfu Duygun; Pınar Karabacak (Literacy Trek, 2022)
This descriptive qualitative study aimed to investigate the types and sources of errors committed by Turkish students learning English as a foreign language (EFL) in their foreign language (L2) writings as well as find out whether there is a difference in terms of the number, classification, and sources of errors between students at two different proficiency levels. To this end, the study was carried out at the School of Foreign Languages at a non-profit foundation university in Turkey in the 2020-2021 academic year. The students participating in the study (N= 32), who were selected using the convenient sampling method and participated in the study voluntarily, were Turkish preparatory class students having two different English proficiency levels, namely A1 level (n= 16) and A2 level (n= 16). Data for the study came from three different narrative paragraphs (each ranging in a 100 - 200 word band) written by the students, and a total of 96 paragraphs were collected for the study. The analysis revealed that the most frequent type of error was grammatical errors overall, a large part of which was the inappropriate use of verb forms. Moreover, findings concerning the potential differences between two proficiency levels showed that A1 level learners committed more errors than A2 level learners in all types except the semantic errors. Based on these findings, a number of implications for L2 writing teachers are discussed.